Penerapan Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Pada Elemen Rencana Biaya Serta Penjadwalan Konstruksi Bangunan Di SMK Negeri 4 Pariaman - Elvani Tanjung; Laras Oktavia Andreas (Jurnal Vokasi Mekanika (VoMek), 2025)
The problems that arise in the element of Building Construction Costing and Scheduling Plan include the incompatibility of the use of learning models applied by teachers with the characteristics of the independent curriculum. Low student learning outcomes are a factor in choosing the PjBL learning model. This research was conducted to determine how effective the PjBL learning model is in order to improve student learning outcomes through the Building Construction Costing and Scheduling Plan element. The type of research used is PTK, with the research subjects used being 7 people in the 2024/2025 school year. For the test of test questions, it has been carried out on class XI DPIB 2 students at SMKN 1 Pariaman with 21 respondents. This study shows that PjBL can improve student learning outcomes in the material of calculating floor work. This is indicated by student learning scores on the pre-test (before action) with an average obtained of 59.29. While in cycle 1 an average of 69.29 was obtained, it increased in cycle 2 to 82.86. In addition, the student learning completeness rate increased to 100% in cycle 2 after the action was taken. Therefore, this study proves that the PjBL model can improve the learning achievement of class XI DPIB students on the elements of the Cost Plan and Scheduling of Building Construction at SMKN 4 Pariaman.